Marketing Brexit: An exploratory study of young voter engagement in relation to the EU referendum. (November 2018) - Pich, Christopher; Harvey, John; Armannsdottir, Guja; Poorrezaei, Mojtaba; Branco-Illodo, Ines; Kincaid, Andrew
This article presents a study of young voter engagement in relation to the EU referendum—a democratic vote on the United Kingdom's membership of the European Union. Using the marketing concept of engagement, we examine how young voters engaged cognitively, emotionally, and behaviorally with the referendum and its associated campaigns. A mixed-method study combining multiple-phase questionnaires, longitudinal social network analysis of Twitter, and sentiment analysis provides a rich empirical description of young voter engagement. The findings reveal that young voter engagement is multi-faceted and varies enormously across our sample, particularly for behavioral engagement online. We subsequently question the analytical relevance of the engagement construct for political marketing before developing a typology to classify young voters according to the variance and extent of their specific engagement profile, which we define as "Prototypical Engagement Persona." We conclude the article by presenting an agenda for future research on young voter engagement.